Robust Speed Tracking Control of Permanent Magnet Synchronous Linear Motor Based on a Discrete-Time Sliding Mode Load Thrust Observer - Wang, Lijun; Zhao, Jiwen; Zheng, Zhilei (IEEE transactions on industry applications, 2022)
In this article, we proposed a discrete-time sliding mode load thrust observer to reduce the influence of load thrust mutation on the linear motor and improve the antiinterference ability and speed tracking performance of the system. First, the electrical and dynamic models of linear motor are established, and the limitation of conventional double-closed-loop control based on proportional integral (PI) algorithm is analyzed. Second, the extended state equation of velocity and load thrust is given and an improved sliding mode reaching law is designed to establish the discrete-time load thrust observer. Based on Lyapunov theory, the stability of the observer is proved. The observed load thrust is compensated to the controller in the form of feedforward. Finally, a series of comparative experiments were carried out. The experimental results show that compared with the PI control, the maximum speed fluctuation of this method is reduced by about 18.1% when the load changes between no-load and rated load. This means that the method in this article can effectively improve the antidisturbance ability of the system.